ASPECTS OF STRING PHENOMENOLOGY IN PARTICLE PHYSICS AND COSMOLOGY - Antoniadis, I. (Одеські астрономічні публікації, 2016)
We discuss possible connections between several scales in particle physics and cosmology, such the the electroweak, inflation, dark energy and Planck scales. We then describe the phenomenology of a model of supersymmetry breaking in the presence of a tiny (tunable) positive cosmological constant. The model is coupled to the MSSM, leading to calculable soft supersymmetry breaking masses and a distinct low energy phenomenology that allows to differentiate it from other models of supersymmetry breaking and mediation mechanisms.